An Embodied Existence in Heaven and the Non-Cartesian Substance Dualism - Perez, Alejandro (TheoLogica: An International Journal for Philosophy of Religion and Philosophical Theology, 2021)
In this paper, I propose to imagine, through Non–Cartesian substance dualism (NCSD), how we could resurrect. Even though many objections have been addressed to the classic conception of eschatology since the beginning of the century of eschatology, I propose we have some reasons to think that a more corporeal conception of the eschaton is not only desirable but also metaphysically possible and compatible with biblical data. I shall explore what I call the Christ Body Argument, which invites us to reject, on the one hand, a disembodied existence in heaven, and on the other side to adopt a corporeal existence of Christ in heaven. A kind of Dualism, and more precisely, one possessing NCSD’s virtues, could play a role in exploring this new theological option. I expect to show that NCSD is a metaphysical option allowing us to understand better what we are. If we hope and believe in the resurrection of the dead, NCSD provides an interesting model to think about it.